Prognostic information derived from RT‐PCR analysis of peritoneal fluid in gastric cancer patients: Results from a prospective multicenter clinical trial. Issue 2 (24th October 2013) - Tamura, Shigeyuki; Fujiwara, Yoshiyuki; Kimura, Yutaka; Fujita, Junya; Imamura, Hiroshi; Kinuta, Masakatsu; Yano, Masahiko; Hiratsuka, Masahiro; Kobayashi, Kenji; Okada, Kaoru; Mori, Masaki; Doki, Yuichiro
Abstract Objective The purpose of this study is to define the clinical significance of the molecular analysis of peritoneal lavage fluid in patients with gastric cancer in a multicenter prospective trial. Methods Quantitative RT‐PCR with CEA and CK‐20 mRNA as target markers was introduced for peritoneal lavage diagnosis in 141 patients with clinically advanced gastric cancer from 9 different institutes. We then evaluated the prognostic factors in patients and also evaluated predictive markers for peritoneal recurrence in 124 patients without peritoneal metastasis at surgery Results Out of the 141 cases, 140 patients were successfully analyzed by RT‐PCR of peritoneal lavage fluids. According to multivariate analysis, the combined results of RT‐PCR (CEA and CK‐20) and CK‐20 alone in addition to pathological N (pN)‐stage were significantly correlated with overall survival. Multivariate analysis showed that the RT‐PCR (CEA and CK‐20) and CEA alone in addition to pathological T‐stage, pN‐stage, and histological grade were significantly correlated with peritoneal recurrence after surgery. Conclusion This is the first multicenter prospective study to show that RT‐PCR analysis of peritoneal lavage fluid with the combination of CEA and CK‐20 markers was useful for predicting overall survival and peritoneal recurrence in patients with clinically advanced gastric cancer. J. Surg. Oncol. 2014 109:75–80. © 2013 Wiley Periodicals, Inc.